Optimizing SDN Controller to Switch Latency for Controller Placement Problem - Zobary, Firas (Informatica, 2024)
Software-Defined Networking (SDN) revolutionizes network flexibility by decoupling the data plane from control planes, employing a logically centralized yet physically distributed multi-controller architecture. The optimal placement of controllers and their quantity presents a significant challenge known as the Controller Placement Problem (CPP). This study addresses the optimization of average propagation delay between controllers and switches, introducing an enhancement version of well-known K-Means algorithm for network partitioning and controller placement, called an Advanced K-Means algorithm. The proposed algorithm strategically minimizes the average propagation delay by situating controllers in optimal nodes within each sub-network. Evaluation through simulations on the Internet OS3E topology demonstrates the algorithm's efficacy, showcasing a 22%, 11%, 7%, and 3% reduction in average propagation delay compared to DBCP, POCO, CNPA, and HDIDS, respectively. These results establish the proposed algorithm as a competitive solution, emphasizing its capacity to achieve comparable or superior performance in mitigating latency between controllers and switches when compared to existing algorithms.